2019
DOI: 10.1055/s-0039-1688504
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Soft Tissue Balance/Kinematics and Clinical Evaluation of Modified Kinematically versus Mechanically Aligned Total Knee Arthroplasty

Abstract: AbstractRecently, kinematically aligned total knee arthroplasty has been found to achieve better clinical outcomes than mechanically aligned TKA. Despite the good clinical outcomes that are reported at short- to mid-term follow-up, intraoperative variables that are associated with a better outcome have not been measured. Therefore, this study was conducted to compare intraoperative kinematics/soft tissue balance and the clinical outcomes of patients who underwent modified kinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
2
18
1
Order By: Relevance
“…However, we also discovered no significant differences in KSS (function) between the KA and MA groups (MD = 4.86, 95% CI − 0.50 to 10.23, I 2 = 72%, Fig. 3 c) [ 19 , 20 , 24 – 26 , 29 , 30 , 34 ]. After gradually removing these eight studies, we found no significant change in heterogeneity, indicating that the pooled analysis results of KSS (function) were stable (Table 2 ).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…However, we also discovered no significant differences in KSS (function) between the KA and MA groups (MD = 4.86, 95% CI − 0.50 to 10.23, I 2 = 72%, Fig. 3 c) [ 19 , 20 , 24 – 26 , 29 , 30 , 34 ]. After gradually removing these eight studies, we found no significant change in heterogeneity, indicating that the pooled analysis results of KSS (function) were stable (Table 2 ).…”
Section: Resultsmentioning
confidence: 60%
“…As shown in Fig. 3 a, eight studies with 572 patients were included in the KSS (knee) evaluation [ 19 , 20 , 24 , 25 , 27 , 29 , 30 , 34 ]. The pooled MD was 3.24 (95% CI 0.46–6.03), and I 2 was 59%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinematic path of the medial pivot pattern was substantially confirmed in MA-TKA but was much smaller than that in normal healthy knees [ 18 ]. Based on the perspectives of intraoperative gap balance, greater tibial internal rotation and lateral laxity during knee flexion were observed in KA-TKA than in MA-TKA [ 19 ]. In our study, the degree of medial pivot motion seemed sufficient in KA-TKA using a medial pivot knee prosthesis, but paradoxical femoral anterior sliding at early flexion still existed.…”
Section: Discussionmentioning
confidence: 99%
“…7 According to Matsumoto et al, kinematically aligned cruciate retaining TKA maintained more tibial internal rotation and lateral laxity during flexion than mechanically aligned TKA. 25 Even though meticulous TKA studies have been conducted, it is necessary to understand the relationship between the soft tissue laxity and kinematics in normal knee. In this study, the rotation angle of the tibia was correlated to the intermediate angle of IE laxity at 0°, 30°, 60°, and 90° of knee flexion, and the coronal alignment of the lower limb also correlated to the intermediate angle of VV laxity.…”
Section: Discussionmentioning
confidence: 99%